Peran Lembaga Keuangan Syariah dalam Mendukung Kemandirian Ekonomi Masyarakat Desa: Studi Kasus Desa Sila Rato Kecematan Bolo Kabupaten Bima - Sahrul; Umar Sagaf; Ibrahim (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Rural communities have a desire to live a decent life, so they make efforts to advance the businesses they run to achieve these goals. Where in the process of advancing the business is not always smooth. It is not uncommon for people to need an injection of funds to finance their business. Islamic financial institutions are present in rural communities, especially in Sila Rato Village to help finance business activities run by the community. Therefore, the purpose of this research is to find out the role of Islamic financial institutions in supporting the economic independence of the community, especially in Sila Rato village. The type of research is qualitative research. Then the data collection techniques used are observation, interview and documentation. The research location is Rato Sila Village, Bima Regency, West Nusa Tenggara. Data analysis techniques use data reduction, data presentation and conclusion drawing. Based on the results of the study, Islamic financial institutions have played a significant role in encouraging the economic independence of the Sila Rato Village community by providing financial resources that can be accessed easily and in accordance with sharia. The existence of these institutions not only improves economic welfare, but also strengthens social ties and solidarity among community members through financing based on the principles of mutual cooperation and risk sharing. Thus, Islamic financial institutions have a positive impact on the community.